Perrault syndrome with amenorrhea, infertility, Tarlov cyst, and degenerative disc. (2nd December 2019) - Al-Jaroudi, Dania; Enabi, Saed; AlThagafi, Malak Sameer
Abstract: Perrault syndrome is a rare autosomal recessive disorder that affects both males and females. The syndrome causes deafness in males, however females display gonadal dysgenesis along with sensorineural hearing loss. Herein, we present a 27-year-old female patient who is deaf and mute along with primary amenorrhea. Hormonal assays revealed hypergonadotropic hypogonadism and the karyotype was 46 XX. Pelvic ultrasound described a hypoplastic uterus and streak ovaries. MRI of the spine showed degenerative discs and Tarlov cysts. Whole exome sequencing identified a LARS2 mutation and the patient was diagnosed with Perrault syndrome type four ( PRLTS4 ).